Electrode manufacturing method and electrode

By forming grooves on battery electrodes using a pulsed laser with specific conditions, the method addresses insufficient electrolyte penetration, enhancing electrolyte flow and reducing reaction resistance through nanostructures on the electrode's surface.

JP7605197B2Active Publication Date: 2024-12-24TOYOTA JIDOSHA KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022142946
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-08
Publication Date
2024-12-24
Estimated Expiration
2042-09-08

AI Technical Summary

Technical Problem

Existing battery electrodes with active material layers face issues of insufficient electrolyte penetration, leading to deteriorated cycle characteristics, and there is a need for further performance improvements beyond just promoting electrolyte flow.

Method used

The method involves forming grooves on the active material layer using a pulsed laser with a pulse width of 200 ns or less, under atmospheric pressure of 980 hPa or higher, and an assist gas wind speed of 5 m/s or less, which generates nanostructures on the groove's inner surface, increasing the surface area and promoting electrolyte penetration.

Benefits of technology

The deposition of nanostructures on the groove's inner surface enhances electrolyte penetration through capillary action, significantly increasing the reaction area and reducing reaction resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605197000002
    Figure 0007605197000002
  • Figure 0007605197000003
    Figure 0007605197000003
  • Figure 0007605197000004
    Figure 0007605197000004
Patent Text Reader

Abstract

To reduce reaction resistance.SOLUTION: (a) An active material layer is formed. (b) A groove is formed on a surface of the active material layer by performing laser processing on the surface of the active material layer. In the laser processing, a pulsed laser with a pulse width of 200 ns or less is used. The atmospheric pressure is 980 hPa or more and the assist gas has a wind speed of 5 m / s or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for manufacturing an electrode, and to an electrode. [Background technology]

[0002] Japanese Patent Laid-Open Publication No. 2013-097925 (Patent Document 1) discloses forming recesses by irradiating the surface of an active material layer with a laser. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-097925 A Summary of the Invention [Problem to be solved by the invention]

[0004] Generally, a battery electrode includes an active material layer. The active material layer is porous. An electrolyte solution can permeate into the active material layer. If the electrolyte solution does not permeate sufficiently, for example, cycle characteristics and the like may be reduced. In order to promote the electrolyte solution permeation, it has been proposed to form grooves (recesses) on the surface of the active material layer. That is, the grooves serve as paths for the electrolyte solution, which can promote the electrolyte solution permeation. However, there is a demand for further performance improvement in addition to improvements in cycle characteristics.

[0005] Therefore, an object of the present disclosure is to reduce reaction resistance. [Means for solving the problem]

[0006] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.

[0007] 1. A method for producing an electrode includes the following steps (a) and (b): (a) An active material layer is formed. (b) A groove is formed on the surface of the active material layer by performing laser processing on the surface of the active material layer. In the laser processing, a pulse laser having a pulse width of 200 ns or less is used. The atmospheric pressure is 980 hPa or more. And the wind speed of the assist gas is 5 m / s or less.

[0008] In general, in laser processing, by-products may be generated due to the deterioration of the processing object. The by-products may accumulate in the processing area. Usually, the by-products are removed from the viewpoint of preventing contamination. That is, the by-products may be removed by blowing them away with the assist gas used in laser processing. In addition, in a reduced pressure atmosphere, the by-products may be removed by suction.

[0009] Conventionally, it has been proposed to form grooves using, for example, a microsecond pulsed laser. According to the new findings of the present disclosure, nanostructures can be generated as by-products by irradiating an active material layer with a pulsed laser having a pulse width of 200 ns or less. The nanostructures can be easily removed by an assist gas or the like.

[0010] However, under certain conditions, the nanostructures may be deposited on the inner surface of the groove without being removed. According to further findings of the present disclosure, the deposition of the nanostructures on the inner surface of the groove is expected to reduce the reaction resistance. The deposition of the nanostructures may significantly increase the surface area of ​​the active material layer. In other words, it is believed that the reaction area may be significantly increased and the reaction resistance may be reduced.

[0011] Furthermore, the penetration of the electrolyte can be further promoted, presumably because the aggregate of nanostructures forms minute irregularities on the inner surface of the groove, which generates a capillary phenomenon.

[0012] 2. In the method for manufacturing an electrode according to the above item "1," a nanostructure may be generated by modifying the surface of the active material layer by irradiating the active material with a pulsed laser. The nanostructure may be deposited on the inner surface of the groove to form a nanostructure layer.

[0013] The formation of the nanostructure layer is expected to promote capillary action, for example.

[0014] 3. The electrode includes an active material layer. A groove is formed in the surface of the active material layer. At least a part of the inner surface of the groove is covered with a nanostructure layer. The nanostructure layer includes nanostructures.

[0015] By covering the inner surface of the groove with the nanostructure layer, the surface area of ​​the active material layer can be significantly increased. As a result, it is believed that the reaction area can be increased and the reaction resistance can be reduced. Furthermore, it is expected that capillary action will occur in the nanostructure layer, promoting the penetration of the electrolyte.

[0016] 4. In the electrode described in the above item "3," the nanostructure layer may have a thickness of, for example, 1 to 10 μm.

[0017] 5. In the electrode according to the above item "3" or "4," the nanostructure may have a Feret's diameter of, for example, 10 to 300 nm.

[0018] 6. In the electrode according to any one of the above items "3" to "5", the active material layer has a first chemical composition, and the nanostructure has a second chemical composition, the second chemical composition having a smaller composition ratio of oxygen and carbon than the first chemical composition.

[0019] The nanostructure is believed to be formed from the active material layer. During the process of forming the nanostructure, oxygen and carbon, which are components of the active material layer, may be partially lost.

[0020] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the description of the claims. For example, it is originally intended that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic flow chart of a method for producing an electrode in this embodiment. [Diagram 2] FIG. 2 is a schematic diagram of an electrode in this embodiment. [Diagram 3] FIG. 3 is a schematic cross-sectional view of an electrode in this embodiment. [Figure 4] FIG. 4 is a cross-sectional SEM image of the active material layer in No. 1. [Diagram 5] FIG. 5 is a close-up of the nanostructured layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] <Terms and definitions> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.

[0023] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."

[0024] For example, a numerical range such as "m to n%" includes an upper limit and a lower limit. That is, "m to n%" indicates a numerical range of "m% or more and n% or less." Furthermore, "m% or more and n% or less" includes "more than m% and less than n%." Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.

[0025] Unless otherwise specified, the order of execution of the steps, operations, and the like included in various methods is not limited to the order described. For example, the steps may proceed simultaneously. For example, the steps may be performed in sequence.

[0026] Geometric terms (e.g., "parallel," "perpendicular," "orthogonal," etc.) should not be interpreted strictly. For example, "parallel" may deviate slightly from the strict meaning of "parallel." Geometric terms may include, for example, tolerances, errors, etc. in design, work, manufacturing, etc. The dimensional relationships in each drawing may not match the actual dimensional relationships. In order to facilitate understanding of the present disclosure, the dimensional relationships (length, width, thickness, etc.) in each drawing may be changed. Furthermore, some configurations may be omitted.

[0027] All numerical values ​​are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values ​​may be approximations that may vary depending on the application of the disclosed technology. All numerical values ​​may be expressed with significant figures. Measurements may be average values ​​of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.

[0028] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may also be allowed.

[0029] The chemical compositions of the active material layer and the nanostructure (the "first chemical composition" and the "second chemical composition") can be identified by SEM-EDX (Scanning Electron Microscope-Energy Dispersive X-ray Spectrometry).

[0030] The "Ferret diameter" is measured in a two-dimensional image (e.g., SEM image, etc.) of the nanostructure. The arithmetic mean of the maximum Feret diameters in 20 or more nanostructures is considered to be the "Ferret diameter".

[0031] "Electrode" is a collective term for positive and negative electrodes. The electrode may be a positive electrode, a negative electrode, or a bipolar electrode. The electrode is for a battery. A lithium ion battery is just one example of a battery. The present disclosure may be applied to any battery system.

[0032] <Electrode manufacturing method> Fig. 1 is a schematic flow chart of the method for producing an electrode in this embodiment. Hereinafter, the "method for producing an electrode in this embodiment" may be abbreviated as "this production method". This production method includes "(a) formation of an active material layer" and "(b) laser processing".

[0033] 2 is a schematic diagram of an electrode in this embodiment. In this manufacturing method, an electrode 100 is manufactured. The electrode 100 has grooves 1 on the surface of an active material layer 20.

[0034] (a) Formation of active material layer This manufacturing method includes forming an active material layer 20. The active material layer 20 can be formed by any method. For example, the active material layer 20 may be formed on the surface of a substrate 10.

[0035] The substrate 10 supports the active material layer 20. The substrate 10 may be, for example, in the form of a sheet. The substrate 10 may have a thickness of, for example, 5 to 50 μm. The substrate 10 may be, for example, a current collector. The substrate 10 may be, for example, a metal foil. The metal foil may contain, for example, at least one selected from the group consisting of Al, Cu, Ni, Cr, and Fe. The substrate 10 may contain, for example, an Al foil, an Al alloy foil, a Cu foil, or the like.

[0036] For example, the active material layer 20 may be formed by applying a paint to the surface of the substrate 10. For example, the paint may be formed by mixing an active material, a conductive material, a binder, and a dispersion medium. The dispersion medium may contain, for example, water, N-methyl-2-pyrrolidone (NMP), butyl butyrate, tetralin, etc. For example, the paint may be applied by a die coater or the like. For example, the paint may be dried by a hot air drying oven, etc. After the paint is dried, the active material layer 20 may be compressed. For example, the active material layer 20 may be compressed by a roll press device. The active material layer 20 may be formed to have a thickness of, for example, 10 to 1000 μm. The active material layer 20 may be formed to have a density of, for example, 1 to 4 g / cm. 3 The sintered body may be formed to have a density of 0.01 to 0.05.

[0037] The active material causes an electrode reaction. The active material may be a positive electrode active material. The positive electrode active material may contain any components. The positive electrode active material may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, Li(NiCoMnAl)O2, and LiFePO4. For example, in "Li(NiCoMn)O2", "(NiCoMn)" indicates that the total of the composition ratios within the parentheses is 1. As long as the total is 1, the individual component amounts are arbitrary.

[0038] The active material may be a negative electrode active material. The negative electrode active material may contain any components. The negative electrode active material may contain, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, hard carbon, Si, SiO x (0 < x < 2), Si-based alloys, Sn, SnO x (0 < x < 2), Li, Li-based alloys, and Li4Ti5O 12 and may contain at least one selected from the group consisting of. SiO x (0 < x < 2) may be doped with, for example, Mg or the like. A composite material may be formed by supporting an alloy-based active material (such as Si, etc.) on a carbon-based active material (such as graphite, etc.).

[0039] The conductive material can form an electron conduction path within the active material layer 20. The compounding amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the active material. The conductive material may contain any components. The conductive material may contain, for example, at least one selected from the group consisting of carbon black (CB), vapor-grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake (GF). CB may contain, for example, at least one selected from the group consisting of acetylene black (AB), Ketjenblack (registered trademark), and furnace black.

[0040] The binder can bind solid materials together. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the active material. The binder may contain any component. The binder may contain, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), styrene butadiene rubber (SBR), butadiene rubber (BR), and polytetrafluoroethylene (PTFE).

[0041] (b) Laser processing This manufacturing method includes forming grooves 1 on the surface of active material layer 20 by performing laser processing on the surface of active material layer 20. In this manufacturing method, the laser processing is performed under specific conditions. Any laser processing device may be used as long as the specific conditions can be realized.

[0042] The pulse width of the pulse laser is 200 ns or less. If the pulse width exceeds 200 ns, there is a possibility that nanostructures are not generated. The pulse width may be, for example, 100 ns or less, or 50 ns or less. The pulse width may be, for example, 100 fs or more, 10 ps or more, 1 ns or more, or 10 ns or more. When the pulse width is 10 to 100 ns, the amount of nanostructures generated tends to be large.

[0043] The laser processing may be performed in a chamber in which the atmospheric pressure can be controlled. For example, the pressure in the chamber may be reduced by a vacuum pump. The atmospheric pressure is 980 hPa or more. If the atmospheric pressure is less than 980 hPa, the nanostructure may not be deposited and may be discharged outside the system. The atmospheric pressure may be, for example, 1200 hPa or less, 1100 hPa or less, 1050 hPa or less, 1013 hPa or less, or 1005 hPa or less. The atmospheric pressure may be, for example, 980 to 1005 hPa.

[0044] The assist gas may include, for example, air, nitrogen, argon, helium, etc. The wind speed of the assist gas is 5 m / s or less. If the wind speed of the assist gas exceeds 5 m / s, the nanostructures may not be deposited and may be discharged outside the system. The wind speed of the assist gas may be, for example, 3 m / s or less, 1 m / s or less, or zero. That is, an assist gas may not be used during laser processing.

[0045] The laser may be a fundamental wave or a harmonic wave. The wavelength of the laser may be, for example, 100 to 1100 nm. The output of the laser may be, for example, 0.01 to 10 W, or 0.1 to 1 kW. The beam diameter of the laser may be, for example, 1 to 100 μm.

[0046] <Electrode> The electrode 100 can be completed by forming the groove 1 (see FIG. 2). The electrode 100 includes a substrate 10 and an active material layer 20. The active material layer 20 is disposed on the surface of the substrate 10. The active material layer 20 may be disposed on only one side of the substrate 10. The active material layer 20 may be disposed on both the front and back sides of the substrate 10. At the periphery of the electrode 100, the substrate 10 may be exposed from the active material layer 20. For example, a current collecting member (lead, terminal) or the like may be connected to the portion of the substrate 10 exposed from the active material layer 20.

[0047] Grooves 1 are formed on the surface of the active material layer 20. The grooves 1 may be, for example, dot-like depressions. The grooves 1 may be, for example, linear recesses. The grooves 1 may extend, for example, linearly along the surface of the active material layer 20. By having the grooves 1 extend linearly, it is expected that the penetration of the electrolyte solution will be promoted over a wide range. The grooves 1 may extend, for example, linearly. The grooves 1 may extend, for example, curvedly. The grooves 1 may be branched.

[0048] The grooves 1 may extend, for example, so as to cross the surface of the active material layer 20. The grooves 1 may cross the active material layer 20 in the width direction (X-axis direction) or in the length direction (Y-axis direction), for example. The grooves 1 may have openings, for example, on the side surfaces of the active material layer 20. The electrolyte can flow into the grooves 1 from the openings. The formation of the openings can promote the penetration of the electrolyte.

[0049] A single groove 1 may be formed in the active material layer 20, or a plurality of grooves 1 may be formed. The plurality of grooves 1 may be formed, for example, in a line pattern. "Lines" refers to a set of parallel lines. The plurality of grooves 1 may be formed, for example, in a lattice pattern.

[0050] The interval (pitch) between adjacent grooves 1 may be, for example, 0.1 to 10 mm. The length of the groove 1 may be, for example, 1 to 5000 mm, or 1 to 1000 mm.

[0051] FIG. 3 is a schematic cross-sectional view of an electrode in this embodiment. FIG. 3 shows a cross section perpendicular to the direction in which the groove 1 extends (extension direction). The groove 1 may have any cross-sectional shape. The cross-sectional shape of the groove 1 may be, for example, V-shaped, U-shaped, rectangular, trapezoidal, or the like. The cross section of the groove 1 may have, for example, a bottom 1b and a side wall 1s. The bottom 1b may be a plane, a curved surface, or a point. The bottom 1b is connected to two side walls 1s. The two side walls 1s may be, for example, line-symmetric or not line-symmetric. The side wall 1s may extend perpendicular to the surface of the active material layer 20, or may be inclined with respect to the surface of the active material layer 20.

[0052] The width 1w of the opening may be, for example, 10 to 1000 μm, 100 to 500 μm, or 300 to 500 μm. The depth 1d of the groove 1 may be, for example, 10 to 100 μm, or 50 to 100 μm. The ratio of the depth 1d of the groove 1 to the thickness 20t of the active material layer 20 may be, for example, 0.1 to 0.9, or 0.3 to 0.7.

[0053] At least a portion of the inner surface of groove 1 is covered with nanostructure layer 2. Nanostructure layer 2 may cover the entire inner surface of groove 1. Nanostructure layer 2 may cover a portion of the inner surface of groove 1. Nanostructure layer 2 may extend to the outside of groove 1. Nanostructure layer 2 may extend so as to cover a portion of the surface of active material layer 20. Nanostructures may not be present in active material layer 20 except for the inner surface of groove 1.

[0054] Nanostructure layer 2 is an assembly of nanostructures. Nanostructure layer 2 can be formed by depositing nanostructures on the inner surface of groove 1. Nanostructure layer 2 may have a thickness of, for example, 1 to 10 μm, or 3 to 10 μm.

[0055] The nanostructure layer 2 may have nano-level unevenness. The formation of the nanostructure layer 2 may significantly increase the reaction area, which is expected to reduce reaction resistance. Furthermore, the occurrence of capillary action in the nanostructure layer 2 is expected to promote the penetration of the electrolyte.

[0056] The individual nanostructures forming the nanostructure layer 2 may have any shape. The nanostructures may be, for example, nanoparticles. The nanostructures may be, for example, spherical, rod-shaped, flake-shaped, or fibrous. That is, the nanostructures may be, for example, nanospheres, nanorods, nanocubes, nanoplates, nanofibers, nanotubes, etc. The individual nanostructures may be separate and independent from each other. Adjacent nanostructures may be bonded to each other.

[0057] The nanostructure may have a Feret's diameter of, for example, 10 to 300 nm, or 50 to 150 nm. The nanostructure may form nano-level unevenness. The pitch of the unevenness formed by the nanostructure (the distance between adjacent protrusions) may be, for example, 10 to 300 nm.

[0058] The nanostructures may have a different chemical composition than the active material layer 20. That is, the active material layer 20 has a first chemical composition. The nanostructures have a second chemical composition. The second chemical composition may have a smaller composition ratio of oxygen and carbon than the first chemical composition. For example, when the electrode 100 is a positive electrode, the second chemical composition may have a larger composition ratio of transition metals (e.g., Ni, Co, Al, etc.) than the first chemical composition.

[0059] It is believed that the change in chemical composition is caused by the irradiation of the pulsed laser. For example, the composition ratio of oxygen may decrease due to the release of part of oxygen from the positive electrode active material. For example, the composition ratio of carbon may decrease due to the release of part of carbon from the conductive material. EXAMPLES

[0060] <Sample preparation> (a) Formation of active material layer The following materials were prepared: Base material: Al foil Active material: Li(NiCoMn)O2 Conductive material: AB Binder: PVdF Dispersion medium: NMP

[0061] The active material, the conductive material, the binder, and the dispersion medium were mixed to form a coating material, which was then applied to the surface of the substrate to form an active material layer.

[0062] (b) Laser processing Electrodes Nos. 1 to 10 were manufactured by subjecting the surface of the active material layer to laser processing under various conditions (see Table 1 below).

[0063] <Evaluation> The cross section of the active material layer was observed with an SEM to confirm the presence or absence of nanostructures. The results are shown in Table 1 below. Furthermore, a test battery including the electrodes was manufactured. The test battery was a lithium ion battery. The battery performance of the test battery was confirmed. The results are shown in Table 1 below.

[0064] [Table 1]

[0065] <Result> No nanostructures were observed in Nos. 2 and 3. It is believed that the nanostructures were expelled from the system by evacuation because the atmospheric pressure was less than 980 hPa.

[0066] No nanostructures were observed in Nos. 6, 7, and 9. It is believed that the wind speed of the assist gas exceeded 5 m / s, causing the nanostructures to be blown away and expelled from the system.

[0067] No nanostructures were observed in No. 10. In No. 10, a pulsed laser with a pulse width exceeding 200 ns was used.

[0068] Nanostructures were confirmed on the inner surface of the groove in No. 1, 4, 5, and 8. In these samples, the pulse width was 200 ns or less, the atmospheric pressure was 980 hPa or more, and the wind speed of the assist gas was 5 m / s or less. No. 1, 4, 5, and 8 (with nanostructures) had improved battery performance compared to No. 2, 3, 6, 7, 9, and 10 (without nanostructures).

[0069] 4 is a cross-sectional SEM image of the active material layer in No. 1. Grooves 1 are formed on the surface of active material layer 20. Nanostructure layer 2 covers the inner surface of groove 1. Nanostructure layer 2 has a thickness of 1 to 10 μm.

[0070] FIG. 5 is an enlarged image of the nanostructure layer. The nanostructure layer 2 is an aggregate of nanostructures. Each nanostructure has a Feret diameter of 10 to 300 nm. The nanostructure layer 2 has nano-level irregularities. It is believed that the formation of the nanostructure layer 2 significantly increases the surface area, thereby reducing reaction resistance and improving battery performance.

[0071] The chemical composition of the nanostructure had a smaller composition ratio of oxygen and carbon than the chemical composition of active material layer 20 . [Explanation of symbols]

[0072] 1 groove, 1b bottom, 1d depth, 1s sidewall, 1w width, 2 nanostructure layer, 10 substrate, 20 active material layer, 20t thickness, 100 electrode.

Claims

1. (a) forming an active material layer; and (b) forming grooves in the surface of the active material layer by performing laser processing on the surface of the active material layer; Including, In the laser processing, A pulsed laser having a pulse width of 200 ns or less is used, The atmospheric pressure is 980 hPa or more, and The wind speed of the assist gas is 5 m / s or less. A method for manufacturing an electrode.

2. The surface of the active material layer is modified by the irradiation of the pulsed laser, A nanostructure is produced, and The nanostructures are deposited on the inner surface of the groove to form a nanostructure layer. A method for producing the electrode according to claim 1 .

3. An active material layer is included, A groove is formed on the surface of the active material layer, At least a portion of the inner surface of the groove is coated with a nanostructured layer; the nanostructure layer includes nanostructures; the active material layer has a first chemical composition; the nanostructures have a second chemical composition; The second chemical composition has a smaller composition ratio of oxygen and carbon than the first chemical composition. electrode.

4. The nanostructure layer has a thickness of 1 to 10 μm.

4. The electrode of claim 3.

5. The nanostructure has a Feret diameter of 10 to 300 nm.

4. The electrode of claim 3.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode and preparation method thereof and lithium ion battery

    CN110085806A

  • Method for manufacturing electrode for lithium secondary battery, electrode for lithium secondary battery, and lithium secondary battery

    JP2013097925A

  • Silicon structure body, manufacturing device of silicon structure body and manufacturing method of silicon structure body

    JP2017206401A

  • Two-layer structure electrode and its manufacturing method

    JP2018537839A

  • Electrode, manufacturing method thereof, and lithium ion secondary battery

    JP2019036497A